1993
DOI: 10.1002/jca.2920080204
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of paraprotein‐associated peripheral polyneuropathies by immunoadsorption of plasma with staphylococcal protein A

Abstract: Two patients with paraprotein-associated peripheral polyneuropathy were treated successfully using immunoadsorption of patient's plasma with staphylococcal protein A. Both had previously been treated with immunosuppressive agents or plasma exchange, and were rapidly relapsing at the time of their protein A immunoadsorption therapy. One patient was treated "on-line" with a blood cell separator, and one was treated "off-line." Both responded well to therapy with minimal toxicity. Serum levels of circulating immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our patients who have responded to Prosorba column treatment [12] have had mainly demyelinating sensorimotor peripheral polyneuropathies without prominent axonal signs or denervation. The associated monoclonal paraproteins have been of all major immunoglobulin classes.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our patients who have responded to Prosorba column treatment [12] have had mainly demyelinating sensorimotor peripheral polyneuropathies without prominent axonal signs or denervation. The associated monoclonal paraproteins have been of all major immunoglobulin classes.…”
Section: Discussionmentioning
confidence: 92%
“…The response of two of our three patients to Prosorba treatment suggests that removal of pathogenetic IgG paraproteins cannot be the sole mechanism of action in these patients given that their paraproteins were of the IgM and IgA class respectively. Previous reported experience with polyneuropathies treated using Prosorba columns suggested that activation of complement and/or enhanced clearance of soluble immune complexes from the plasma may occur [12,22].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations